Zolpidem induces paradoxical metabolic and vascular changes in a patient with PVS. (5th August 2013) - Rodriguez-Rojas, Rafael; Machado, Calixto; Álvarez, Lázaro; Carballo, Maylen; Estevez, Mario; Perez-Nellar, Jesus; Pavon, Nancy; Chinchilla, Mauricio; Carrick, Frederick R.; DeFina, Philip
Abstract: Introduction : Zolpidem is a non-benzodiazepine drug used for the therapy of insomnia, which has selectivity for stimulating the effect of GABA-A receptors. Recently, a paradoxical arousing effect of zolpidem in patients with severe brain damage has been repeatedly reported. Methods : A placebo-controlled magnetic resonance study was conducted to evaluate its effect on BOLD and metabolites spectral signals in a patient with severe brain injuries and an age-matched healthy volunteer. A multi-modal analysis was used to assess aspects in the pharmacologically-induced changes in the resting-state brain metabolism. Results : A significantly increased BOLD signal was transiently localized in the left frontal cortices, bilateral anterior cingulated areas, left thalamus and right head of the caudate nucleus. The healthy subject showed a deactivation of the frontal, parietal and temporal cortices. BOLD signal changes were found to significantly correlate with concentrations of extravascular metabolites in the left frontal cortex. It is discussed that, when zolpidem attaches to modified GABA receptors of neurodormant brain cells, brain activation is induced. This might explain the significant correlations of BOLD signal changes and proton-MRS metabolites in this patient after zolpidem. Conclusion : It was concluded that proton-MRS and BOLD signal assessment could be used to study zolpidem-induced metabolic modulation in a resting state.